Electronic Voting Machine Using FPGA - Prasad, P.P.M.; Chaitanya, T. Krishna; Kalyan, Koda; Tejaswini, Gutti Naga; RizwanaBanu, Shaik; Muzamilahamad, Shaik (Engineering Research: Perspectives on Recent Advances Vol. 6, 2025)
Nowadays conducting elections is very difficult and it is a very large process. To prevent election tampering, electronic voting machines are essential in a democratic society. Voting was formerly conducted using ballot sheets in an antiquated manner, which leaves plenty of room for fraud. Voting machines also have a difficult task to conduct voting. People believe that machines also tamper with different parties. In this work, we have examined a digital electronic voting system that was created with the Xilinx tool's VHDL coding. There is an enable switch available to initiate the voting process. In the electoral process, four candidates—Button 1(Party1), Button2(Party 2), Button 3(Party 3) and Button4(Party 4) —are taken into consideration. V switch is a 2-bit signal that voters use to select a contestant to support. Voting will not take place until enable is activated, as indicated by the invalid signal that appears if a voter attempts to cast a ballot without enable engaged. In order to preserve integrity throughout the entire process, electronic voting machines are essential for elections at the college, panchayat, state, national, and international levels.